Accountability Guidance and Counseling Program In the City of Banjarmasin Vocational School - Muhammad Yuliansyah; I Nyoman Sujana Degeng; Bambang Budi Wiyono; Achmad Supriyanto; Jarkawi Jarkawi; Murdiansyah Herman (International Journal of Social Science and Religion (IJSSR), 2021)
The existence of guidance and counseling is a basic need that must be prioritized in the life of the community Guidance and Counseling Services that are good and right, effective and efficient in developing guidance and counseling missions so that community recognition and trust will increase. Accountability is carried out periodically and in accordance with the provisions with effective documentation through measurement of results from professional activities. Accountability refers to accountability for the success or failure of achieving the results of an organization's program. The guidance and counseling profession as professional counselors masters and realizes their professional practice, the accountability of guidance and counseling must be carried out as an embodiment of the obligation to account for the success or failure of implementing the guidance and counseling program mission in achieving the stated goals and objectives.